EBV T-cell immunotherapy generated by peptide selection has enhanced effector functionality compared to LCL stimulation - Cooper, Rachel S.; Sutherland, Catherine; Smith, Linda M.; Cowan, Graeme; Barnett, Mark; Mitchell, Donna; McLean, Colin; Imlach, Stuart; Hayes, Alan; Zahra, Sharon; Manchanayake, Champa; Vickers, Mark A.; et al. (Frontiers in Immunology, 2024)
Adoptive immunotherapy with Epstein-Barr virus (EBV)-specific T cells is an effective treatment for relapsed or refractory EBV-induced post-transplant lymphoproliferative disorders (PTLD) with overall survival rates of up to 69%. EBV-specific T cells have been conventionally made by repeated stimulation with EBV-transformed lymphoblastoid cell lines (LCL), which act as antigen presenting cells. However, this process is expensive, takes many months and has practical risks associated with live virus. We have developed a peptide-based, virus-free, serum-free closed system to manufacture a bank of virus-specific T cells (VST) for clinical use. We compared these with standard LCL-derived VST using comprehensive characterization and potency assays to determine differences that might influence clinical benefits. Multi-parameter flow cytometry revealed peptide-derived VST had an expanded central memory population and less exhaustion marker expression than LCL-derived VST. A quantitative HLA-matched allogeneic cytotoxicity assay demonstrated similar specific killing of EBV-infected targets, though peptide-derived EBV T cells had significantly higher expression of antiviral cytokines and degranulation markers after antigen recall. High throughput T cell receptor-beta (TCRβ) sequencing demonstrated oligoclonal repertoires, with higher complementary determining region 3 (CDR3) sequence matching to EBV in peptide-derived EBV T cells. Peptide-derived products showed broader and enhanced specificities to EBV nuclear antigens (EBNAs) in both CD8 and CD4 compartments, which may improve targeting of highly-expressed latency antigens in PTLD. Importantly, peptide-based isolation and expansion allows rapid manufacture and significantly increased product yield over conventional LCL-based approaches.